Effectiveness of Virtual Reality-Based Training on Shooting Performance among BOA SORTE FC Futsal Players - Luca Gabriel Guterres (Universitas Pejuang Republik Indonesia, 2026)
Background: Futsal is characterized by high-intensity intermittent actions requiring rapid perception, decision-making, technical precision, and shooting accuracy. Conventional shooting training improves technical execution but often lacks the perceptual and cognitive demands experienced during competitive matches. Virtual Reality (VR)-based training has emerged as an innovative training modality capable of providing immersive and representative learning environments that integrate perceptual, cognitive, and motor components simultaneously.. Objective: This study aimed to examine the effectiveness of an eight-week Virtual Reality-based training program on shooting performance among BOA SORTE FC futsal players from Timor-Leste. Methods: A quasi-experimental pretest–posttest control group design was employed involving twenty-four male futsal players from BOA SORTE FC (age 18–24 years). Participants were allocated into a Virtual Reality Training Group (n = 12) and a Conventional Training Group (n = 12). Both groups completed three training sessions per week for eight weeks. The VR group performed immersive shooting simulations using VR technology integrated with decision-making tasks, whereas the control group received conventional shooting drills. Shooting accuracy, ball velocity, shooting reaction time, and shooting success percentage were assessed before and after the intervention. Data were analyzed using paired-samples t-tests, independent t-tests, ANCOVA, and Cohen's d effect size with a significance level of p < 0.05. Results: Players receiving Virtual Reality-based training demonstrated significantly greater improvements in shooting accuracy, shooting success percentage, reaction time, and ball velocity compared with the conventional training group (p < 0.05). The largest improvement was observed in shooting accuracy (Cohen's d > 1.20), indicating a large practical effect. Conclusion: Virtual Reality-based training is an effective complementary training strategy for improving shooting performance in competitive futsal players. Integrating immersive perceptual-cognitive practice with conventional technical training provides superior improvements compared with conventional training alone.